2010
DOI: 10.1002/lsm.20894
|View full text |Cite
|
Sign up to set email alerts
|

Detection of melanoma cells in vitro using an optical detector of photoacoustic waves

Abstract: The optical reflectance method provides sensitivity to detect small numbers of melanoma cells without created false-positive signals from pyroelectric interference, showing promise as a means to perform tests for circulating melanoma cells in blood samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…5 Photoacoustic flow cytometry (PAFC) has been used both in vivo and in vitro to detect circulating melanoma cells, which are naturally optically absorbing. 6,7 Most other cancers are nonpigmented and inaccessible to PAFC without cellular alteration. Viator et al 8 demonstrated the ability to add gold nanoparticles (AuNPs) to prostate cancer cells through immunochemistry and detect them using the in vitro cytometry method.…”
Section: Introductionmentioning
confidence: 99%
“…5 Photoacoustic flow cytometry (PAFC) has been used both in vivo and in vitro to detect circulating melanoma cells, which are naturally optically absorbing. 6,7 Most other cancers are nonpigmented and inaccessible to PAFC without cellular alteration. Viator et al 8 demonstrated the ability to add gold nanoparticles (AuNPs) to prostate cancer cells through immunochemistry and detect them using the in vitro cytometry method.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed to detect CTCs in blood samples, including flow cytometry , polymerase chain reaction (PCR) techniques , optical based imaging systems , size and/or density differences , and photoacoustic detection . These methods can be incorporated into microfluidic devices for in vitro measurements .…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, it has been shown that, using an optical detector for the PA waves, it is possible to detect one melanoma cell suspended in saline [11]. In this work, a variant of the PA wave detection is proposed.…”
Section: Introductionmentioning
confidence: 99%